Vitamin D Deficiency Contributes to the Reduction and Impaired Function of Naïve CD45RA+ Regulatory T Cell in Chronic Heart Failure - Yan-hui Ma; Yun-lan Zhou; Chao-yan Yue; Guang-hui Zhang; Lin Deng; Guo-hua Xie; Wei-ping Xu; Li-song Shen (Journal of Immunology Research)
The effect of vitamin D pertinent to cardiovascular health on the heart itself is considered to shift toward an anti-inflammatory response in chronic heart failure (CHF); however, its underlying mechanism is not completely understood. In this study, we demonstrated that plasma 25(OH)D level, negatively associated with NT-ProBNP, correlated with the decreased Treg in CHF compared to the patients with other cardiovascular diseases and healthy and older donors. Naïve Treg cell (CD4+CD45RA+Foxp3loT) subset, rather than whole Treg cells, contributes to the reduction of Treg in CHF. 1,25(OH)2D treatment maintained partial expression of CD45RA on CD4+T cell after αCD3/CD28 monoclonal antibodies activation and ameliorated the impaired CD4+CD45RA+T cell function from CHF patients through upregulating Foxp3 expression and IL-10 secretion in vitro. Low level of vitamin D receptor (VDR) was detected in CD4+CD45RA+T cell of CHF than control, while 1,25(OH)2D treatment increased the VDR expression to exert its immunosuppression on T cell. The results of this study might provide tangible evidence to our knowledge of the impact of vitamin D supplementation on naïve Tregs, which may offer new means of preventing and treating CHF.